Next-Generation Sequencing for the Diagnosis of Challenging Culture-Negative Endocarditis - Kolb, Manon; Lazarevic, Vladimir; Emonet, Stéphane; Calmy, Alexandra; Girard, Myriam; Gaïa, Nadia; Charretier, Yannick; Cherkaoui, Abdessalam; Keller, Peter; Huber, Christoph; Schrenzel, Jacques (Frontiers in Medicine, 2019)
Diagnosis of culture-negative infective endocarditis usually implies indirect pathogen identification by serologic or molecular techniques. Clinical metagenomics, relying on next-generation sequencing is an emerging approach that allows pathogen identification in challenging situations, as evidenced by a clinical case. We extracted DNA from the surgically-removed frozen valve tissue from a patient with suspected infective endocarditis with negative blood and valve cultures. Mapping of the sequence reads against reference genomic sequences, a 16S rRNA gene database and clade-specific marker genes suggested an infection caused by Cardiobacterium hominis.